MANAJEMEN KOMUNIKASI KESATUAN MAHASISWA HINDU DHARMA INDONESIA DALAM PELAKSANAAN PROGRAM KERJA DI ERA PANDEMI COVID-19 - Putu Asrinidevy; I Nyoman Yoga Segara; I Wayan Wastawa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2022)
The COVID-19 pandemic that occurred in Indonesia automatically caused changes in the forms of social and political communication. The beginning of the change is quite disturbing the effectiveness of communication between individuals, groups to institutions and organizations. The problems analyzed in this study is The communication management pattern of the Indonesian Hindu Dharma Student Union in implementing work programs during the COVID-19 pandemic. The theory used as the basis for research analysis, namely Management Theory for the POAC Theory approach and SWOT Analysis Theory for the first and second problems, and Communication Effects Theory for the third problem. This research is a qualitative research with participant observation approach and systematic observation. The data collection technique uses observation and interviews with 5 main informants who have been determined and supported by document collection. Based on the research results, KMHDI applies the POAC system as a communication management pattern. There are supporting factors, namely KMHDI's internal strengths and external opportunities. Meanwhile, the inhibiting factors in communication management in implementing work programs during the COVID-19 pandemic are internal weaknesses and external threats or challenges. Then the communication management carried out by KMHDI in the implementation of the work program has implications internally and externally in various aspects,both cognitive, affective, and behavioral.